THE EFFECT OF USING BLOG TOWARD STUDENTS’ MOTIVATION TO WRITE ANALYTICAL EXPOSITION TEXT - Ratna Dewi; Syahrul Syahrul; Hilma Pami Putri (ELP (Journal of English Language Pedagogy), 2020)
This study was done due to the lack of motivation of students in SMKN Baso to write. One of the media used to increase students’ motivation is blogging. The design of this research was experimental research. The data was obtained through a questionnaire. The populations of this research were the second-grade students at SMKN 1Baso academic years 2019/2020 consisting of 174 students. To determine the sample, the researcher used purposive sampling by choosing two classes, they were XI Perkantoran 1 and XI Perkantoran 2. XI Perkantoran 1 was treated as a control class that applies with conventional media in writing while XI Perkantoran 2 was treated as an experimental class that applies blog in writing. To analyze the data collected, the researcher used the t-test formula to test the hypothesis and consult the result into t-table with level significance α = 0,05. Based on the result of the research, the mean score of the questionnaire after giving the treatment of the experimental class was 72,28 was higher than the mean score of the control class was 65,85. Then it was analyzed by using t-test and the result of t-obtained was 4,47 with the degree of freedom 39 and the level significance α = 0,05. Through comparing the t-obtained (4,47) to t-table (2,042) on the same degree of freedom and level significance, it was found that the value of t-obtained was higher than the value of t-table. Thus the hypothesis (Ha) is accepted which stated using a blog gives a better effect on students’ motivation to write analytical exposition text.